Using a hypothetical scenario to assess public preferences for colorectal surveillance following screening-detected, intermediate-risk adenomas: annual home-based stool test vs. triennial colonoscopy. Issue 1 (December 2016) - Bonello, Bernardette; Ghanouni, Alex; Bowyer, Harriet; MacRae, Eilidh; Atkin, Wendy; Halloran, Stephen; Wardle, Jane; von Wagner, Christian
Abstract Background To assess public preferences for colorectal cancer (CRC) surveillance tests for intermediate-risk adenomas, using a hypothetical scenario. Methods Adults aged 45–54 years without CRC were identified from three General Practices in England (two in Cumbria, one in London). A postal survey was carried out during a separate study on preferences for different first-line CRC screening modalities (non- or full-laxative computed tomographic colonography, flexible sigmoidoscopy, or colonoscopy). Individuals were allocated at random to receive a pack containing information on one first-line test, and a paragraph describing CRC surveillance recommendations for people who are diagnosed with intermediate-risk adenomas during screening. All participants received a description of two surveillance options: annual single-sample, home-based stool testing (consistent with Faecal Immunochemical Tests; FIT) or triennial colonoscopy. Invitees were asked to imagine they had been diagnosed with intermediate-risk adenomas, and then complete a questionnaire on their surveillance preferences. Results 22.1 % (686/3, 100) questionnaires were returned. 491 (15.8 %) were eligible for analysis. The majority of participants stated a surveillance preference for the stool test over colonoscopy (60.8 % vs 31.0 %; no preference: 8.1 %; no surveillance: 0.2 %). Women were more likely to prefer the stool test than men (66.7 % vs. 53.6 %;p = .011). The primary reason for preferring the stool test was that it would be done more frequently. The main reason to prefer colonoscopy was its superiority at finding polyps. Conclusions A majority of participants stated a preference for a surveillance test resembling FIT over colonoscopy. Future research should test whether this translates to greater adherence in a real surveillance setting. Trial registration International Standard Randomised Controlled Trial Number registry, ISRCTN85697880, prospectively registered on 25/04/2013